Therapy for Baby Blues Syndrome: Medical Integration and Quranic Values at Madina Pratama Clinic Medan - Balqis Nur Afifah; Zulkarnaen Zulkarnaen; Sholahuddin Ashani (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Baby blues syndrome is a term used for feelings of unfounded sadness that occur after a woman gives birth to her baby. This is one of the triggers for baby blues, especially in patients or mothers at the Madina Pratama Clinic, Percut Sei Tuan District, Deli Serdang Regency. The purpose of this study was to (1) describe how baby blues syndrome therapy uses medical integration (2) and describe how baby blues syndrome therapy uses the values of the Qur'an. This research method is qualitative using a descriptive approach. This research was conducted at the Madina Pratama Clinic, Percut Sei Tuan District, Deli Serdang Regency and the time of the study was conducted from January 2024 to March 2024. The main informants of this study were midwives and mothers at the Madina Clinic. The instrument used was an interview through midwives and nurses. The data analysis of this study was by data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that medical therapy is very effective in overcoming baby blues symptoms. However, the addition of the values of the Qur'an in therapy has a very good effect. This shows the importance of integrating medical and spiritual aspects in handling the mother's psychological condition. The conclusion of this study is that baby blues syndrome with medical therapy is by providing nutritional intake such as fruits and vegetables. Adequate rest, support from husband and family, while Al-Quran therapy leads to dhikr to reduce anxiety and stress in the mother. Keywords: Al-Quran Values, Baby Blues Syndrome, Medical Integration, Therapy.